Copperhead (2014), volume 2 ebook - Faerber, Jay (Copperhead (2014), 2016)
What starts out as just another Friday night in Copperhead quickly escalates into a rip-roaring adventure featuring a botched date, a band of outlaws, and a desperate chase across the desert. Collects COPPERHEAD #6-10.. Author: Jay Faerber. Illustrator: Scott Godlewski . 2015 Jay Faerber and Scott Godlewski.